2022
DOI: 10.1002/jimd.12575
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and computational models reveal environmental and metabolic interactions in MMUT‐type methylmalonic aciduria

Abstract: Methylmalonyl-coenzyme A (CoA) mutase (MMUT)-type methylmalonic aciduria is a rare inherited metabolic disease caused by the loss of function of the MMUT enzyme. Patients develop symptoms resembling those of primary mitochondrial disorders, but the underlying causes of mitochondrial dysfunction remain unclear. Here, we examined environmental and genetic interactions in MMUT deficiency using a combination of computational modeling and cellular models to decipher pathways interacting with MMUT. Immortalized fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Ramon et al treated human BJ5ta‐MMUT fibroblasts with a variety of stressors attempting to induce a phenotype. One regimen studied was the addition of methylmalonic acid at concentrations of 100 mM in the culture medium and like the studies in the MMA mice, no phenotype was observed 55 . Additionally, experiments of toxic metabolite addition have not consistently yielded the same results.…”
Section: Limitations Of the Toxic Metabolite Theory As An Explanation...mentioning
confidence: 99%
See 3 more Smart Citations
“…Ramon et al treated human BJ5ta‐MMUT fibroblasts with a variety of stressors attempting to induce a phenotype. One regimen studied was the addition of methylmalonic acid at concentrations of 100 mM in the culture medium and like the studies in the MMA mice, no phenotype was observed 55 . Additionally, experiments of toxic metabolite addition have not consistently yielded the same results.…”
Section: Limitations Of the Toxic Metabolite Theory As An Explanation...mentioning
confidence: 99%
“…Both animal and cellular studies using MMUT deficient models illustrate that metabolites alone are insufficient to generate disease pathophysiology 54,55 . Mice engineered to express Mmut in the hepatocytes from a germline transgene ( Mmut −/− ;Tg Ins‐Alb‐Mut ) are fully rescued from the lethality of the full knock out state but manifest significant methylmalonic acidemia, similar to MMA patients who have received an LT 54 .…”
Section: Limitations Of the Toxic Metabolite Theory As An Explanation...mentioning
confidence: 99%
See 2 more Smart Citations
“…McCorvie et al 5 discuss the complex cooperation of transporters, enzymes and chaperones that are required for the generation and delivery of cobalamin, a cofactor for two human enzymes. This is followed by Ramon et al 6 demonstrating how cellular and computational models help to decipher environmental and metabolic interactions in methylmalonic aciduria, suggesting a compensatory role for increased anaplerosis through glutamine. Next, Head et al 7 outline how precise knowledge about pathophysiology in methylmalonic aciduria has enabled the development of targeted therapy.…”
mentioning
confidence: 97%